2021
DOI: 10.1007/s12144-021-02496-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting employee telecommuting preferences and job outcomes amid COVID-19 pandemic: a latent profile analysis

Abstract: In this two-study research using latent profile analysis (LPA), we investigated intra-individual combinations of conscientiousness, autonomy, self-regulation, and extraversion. Based on these combinations, we designed profiles and explored telecommuting preferences and job outcomes of employees during the COVID-19 pandemic. In Study 1, we recruited 199 participants (77 females, ages ranging from 18 to 65). Results of this study revealed three profiles. One profile scored high on all of the variables and displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…In 2020, about 56% of workers in the United States had a job that could be done from home at least partially because of the fact that their job was knowledge-based and had no physical work requirements [ 9 ]. In a study conducted in 2021, it was seen that 50% of the contract workers preferred to work independently because of the freedom and flexibility it provides [ 10 ]. Also, the majority of millennials who work say they prefer flexible work arrangements, including the ability to work from home [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, about 56% of workers in the United States had a job that could be done from home at least partially because of the fact that their job was knowledge-based and had no physical work requirements [ 9 ]. In a study conducted in 2021, it was seen that 50% of the contract workers preferred to work independently because of the freedom and flexibility it provides [ 10 ]. Also, the majority of millennials who work say they prefer flexible work arrangements, including the ability to work from home [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on career success has long noted the positive implications of a satisfying career [ 26 , 54 ] and the effects of possible negative life events that can threaten it [ 2 , 4 ]. However, with the current ongoing developments, due to flexibility and technological advancements [ 55 , 56 ], as well as crisis, such as the COVID-19 pandemic [ 57 ], career changes are inevitable, becoming less secure, which can be perceived as a threat to employees’ career success [ 10 ]. In line with these findings, our study showed that career insecurity can be a threat to employee career satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Still, most research on this topic are related to nursing, and few telecommuting research have explored the topic of autonomy. For example, two studies demonstrate that telecommuting increases autonomy [ 28 , 29 ], while another depicts that enhanced learning opportunities for telecommuters increase autonomy and morale [ 30 ]. Meanwhile, a paucity of researchers had focused on the telecommuters’ autonomy, meaning that despite the flourishing of telecommuting studies due to COVID-19, most are surveys of the actual conditions of telecommuting, and no researcher has examined autonomy improvement in this context—to the best of our knowledge.…”
Section: Prior Research On Telecommuting In Japanmentioning
confidence: 99%